DISTRIBUSI GEOGRAFIS TUNGAU PARASIT NYAMUK Aedes sp. DI DAERAH ENDEMIS DEMAM BERDARAH DENGUE DI KABUPATEN BANJARNEGARA - Arthur Shepta Laksono; Bambang Heru Budianto; Endang Ariyani Setyowati (Fakultas Biologi | Universitas Jenderal Soedirman, 2014)
Parasitic mites are known as the natural enemy of Aedes sp. that can potentially infect any life stages of the Aedes sp. The parasitic mites’ ability to infect Aedes sp. influence the distribution pattern of parasitic mites. The widespread distribution of Aedes sp. is expected to affect the distribution of parasitic mites. The aims of this study were to determine the taxonomic family of parasitic mites that infected Aedes sp. larvae and to determine the geographical distribution patterns of parasitic mites of Aedes sp. in the endemic area of Dengue Hemorrhagic Fever (DHF) in Banjarnegara District. This study used larvae of Aedes sp. taken from the endemic area of DHF in Banjarnegara District. The study sites were in the Parakancanggah Village, Kutabanjar Village, Krandegan Village, and Sokanandi Village. This study used survey method with purposive sampling technique. Variable observed in this research was the distribution pattern of the parasitic mite of Aedes sp. larvae. Parameter observed included the family and the individual number of parasitic mites on each mosquito larvae, the average value, and the variance. Data were analyzed using mean value and the variance so that the distribution pattern can be determined. The level of parasitic mites’ distribution was analyzed using K' index negative binomial distribution. Results showed that 30 individual of parasitic mite were found from 1429 samples of examined Aedes sp. larvae. The identification result were five families of parasitic mites: Pionidae, Histiostomatidae, Hydryphantidae, Hydrachnidae, and Arrenuridae. The distribution pattern of the parasitic mites was regular, and the highest value of K’ index negative binomial distribution was 1,3225, in the Krandegan Village.